Indigenous Education versus Occupational Skills Acquisition for Sustainable Development: The Igbo Example - Okudo, Afoma Rosefelicia (NIU Journal of Social Sciences, 2018)
In southeastern part of Nigeria, the Igbo people emerged as the most entrepreneurial and skillful group who travelled to various parts of Nigeria and in many cases migrated to other parts of the globe for settlement. In recent years, the rate with which globalization and changes in technology affects the way people work and socialize remains amazing, if conscious effort is not targeted towards preserving national heritage for improved economy, certain skills which our forefathers proudly transferred will gradually become extinct. This paper examined the use of indigenous education for enhancing the younger generationsâ€™ acquisition and development of occupational skills for improved economy especially in the globalized and technology driven era. It also discusses the challenges for effective occupational development towards transferring and preservation of the cultural heritage of the Igbo people of Anambra State (southeastern part) of Nigeria. Purposive sampling technique was used to select 100 entrepreneurs craftsmen (respondents) from seven different occupational and popular skills of the Igbo people namely â€“ Palmwine tapping, Weaving of both brooms and baskets, Fishery, Blacksmithing, Animal rearing, Farming and Woodcarving. The population of the study comprises different artisans from different popular occupational skills of Anambra State (the Igbo people) randomly selected from the twenty-one local government areas of the State. Data was collected using Questionnaires and Observation techniques. Descriptive statistics was used to analyze data collected.  The study found that many challenges are facing the development of occupational skills for sustainable development and improved economy among the artisans; and that the younger generations no longer appreciate and value them as means of livelihood due to migration and urbanization which are inevitable situations in the globalized era. Suggestions and recommendations are made on how to improve those occupational skills so that the younger generations will be motivated to take them, for improved economy . Keywords : The Igbo people; traditional occupational skills; globalization; sustainable development and economic growth; cultural heritage